MESIN PENCACAH RUMPUT UNTUK PAKAN TERNAK - Septian S.M, Revanza; Prakita, Zhiko; Herwandi, Herwandi; Fitri Arriyani, Yang (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2025)
This study aims to design a conceptual model of a grass chopper machine to assist in the preparation of livestock feed. The design process was carried out systematically through several stages, including need identification, functional analysis using the Black Box method, development of alternatives via a morphological chart, and evaluation of concepts using a weighted Likert scale. The analysis produced three conceptual design variants (AVK1, AVK2, and AVK3), which were evaluated based on six criteria: functional achievement, manufacturing time, safety, durability, ease of assembly, and maintenance. Based on the evaluation results, AVK3 was selected as the best concept with the highest total score of 4.45. The outcome of this conceptual design is expected to serve as a reference for the future development of an efficient and ergonomic grass chopper machine suitable for small to medium-scale farmers.